The four vertices of a parallelogram are given by: A ( 0 , 3 ) , B ( 1 0 , 8 ) , C ( 1 2 , 1 2 ) , D ( 2 , 7 ) . We want to map these four points into the four vertices of the unit square: A ′ ( 0 , 0 ) , B ′ ( 1 , 0 ) , C ′ ( 1 , 1 ) , D ′ ( 0 , 1 ) , such the image of A is A ′ , and image of B is B ′ , etc. The transformation is required to be an affinity, i.e., for a vector x , its image is y , where
y = T x + b
for a 2 × 2 matrix T and a 2 × 1 vector b .
Find T and b for the given parallelogram and unit square, and enter the sum S of the absolute values of the four elements of matrix T and the two elements of vector b .
S = i = 1 ∑ 2 j = 1 ∑ 2 ∣ T i j ∣ + i = 1 ∑ 2 ∣ b i ∣
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution! Working from the nice form of A ′ , B ′ , and D ′ saved you a lot of time compared to me.
Let:
T = [ t 1 t 3 t 2 t 4 ] b = [ b 1 b 2 ]
Now:
[ X A ′ Y A ′ ] = T [ X A Y A ] + b
Writing out the equations for each vector and its image gives rise to 8 equations in 6 unknowns ( t 1 , 2 , 3 , 4 , b 1 , 2 ):
X A ′ = t 1 X A + t 2 Y A + b 1 Y A ′ = t 3 X A + t 4 Y A + b 2 X B ′ = t 1 X B + t 2 Y B + b 1 Y B ′ = t 3 X B + t 4 Y B + b 2 X C ′ = t 1 X C + t 2 Y C + b 1 Y C ′ = t 3 X C + t 4 Y C + b 2 X D ′ = t 1 X D + t 2 Y D + b 1 Y D ′ = t 3 X D + t 4 Y D + b 2
Using the first six equations to simultaneously solve for the unknown elements of T and b gives the required answer. The last two equations can be used for a sanity check.
⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ X A ′ Y A ′ X B ′ Y B ′ X C ′ Y C ′ ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ = ⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ X A 0 X B 0 X C 0 Y A 0 Y B 0 Y C 0 0 X A 0 X B 0 X C 0 Y A 0 Y B 0 Y C 1 0 1 0 1 0 0 1 0 1 0 1 ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ ⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ t 1 t 2 t 3 t 4 t 5 t 6 ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ ⟹ ⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ t 1 t 2 t 3 t 4 t 5 t 6 ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ = ⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ X A 0 X B 0 X C 0 Y A 0 Y B 0 Y C 0 0 X A 0 X B 0 X C 0 Y A 0 Y B 0 Y C 1 0 1 0 1 0 0 1 0 1 0 1 ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤ − 1 ⎣ ⎢ ⎢ ⎢ ⎢ ⎢ ⎢ ⎡ X A ′ Y A ′ X B ′ Y B ′ X C ′ Y C ′ ⎦ ⎥ ⎥ ⎥ ⎥ ⎥ ⎥ ⎤
The required answer is:
∣ t 1 ∣ + ∣ t 2 ∣ + ∣ t 3 ∣ + ∣ t 4 ∣ + ∣ b 1 ∣ + ∣ b 2 ∣ = 1 . 9
Problem Loading...
Note Loading...
Set Loading...
It is apparent that finding a transformation from y to x is much easier than the reverse. Express this transformation as x = H y + c Notice that for the linear transformation H y , the image of 0 must be 0 . This is because H 's columns represent the positions of the basis vectors i ^ , j ^ etc, and since a zero vector is 0 i ^ + 0 j ^ , the result must be 0 . However, we know that the image of A ′ = 0 is A = ( 0 3 ) . Thus, ( 0 3 ) = H 0 + c = c To figure out the entries of H , we find where the basis vectors B ′ = i ^ and D ′ = j ^ land following the transformation. H y = x − c H i ^ = B − ( 0 3 ) = ( 1 0 8 ) − ( 0 3 ) = ( 1 0 5 ) H j ^ = D − ( 0 3 ) = ( 2 7 ) − ( 0 3 ) = ( 2 4 ) Therefore, H = ( 1 0 5 2 4 ) Going back to the original equation, we can rearrange to see that y = H − 1 ( x − c ) = H − 1 x − H − 1 c H − 1 = det ( H ) 1 ( 4 − 5 − 2 1 0 ) = 3 0 1 ( 4 − 5 − 2 1 0 ) Finally, y = 3 0 1 ( 4 − 5 − 2 1 0 ) x − 3 0 1 ( 4 − 5 − 2 1 0 ) ( 0 3 ) T = 3 0 1 ( 4 − 5 − 2 1 0 ) b = − 3 0 1 ( − 6 3 0 ) = ( 5 1 − 1 ) S = 3 0 4 + 2 + 5 + 1 0 + 5 1 + 1 = 3 0 5 7 = 1 0 1 9 = 1 . 9